Quality of work life and quality of nursing care - Mahadzirah, Mohamad; Wan Norhayati, Mohamed; Hayatul Safrah, Salleh (Medwell Journals, 2016)
The aim of this study is to examine the influence of quality of work life of nurses on their perceived service quality in Malaysian public hospitals. A total of 292 nurses working in the obstetrics and gynecology and pediatric departments in four public hospitals participated in this study. The confirmatory factor analysis was used to test for factorial validity of the constructs and the structural equation modeling was used to test the goodness of fit of the hypothesized model. The findings of the study supported the hypothesized idea that there is a significant relationship between quality of work life and nursing service quality. The results suggest that quality of work life is able to affect employee performance in terms of delivering quality service. The significant positive relationship between quality of work life and service quality suggests that employees with high quality of work life are able to deliver high quality of service. Therefore, this study concludes that the management of public healthcare organizations need to concentrate on employee quality of work life as that can enhance and facilitate the delivery of quality service to patients.